MODERN METHODS OF MOTIVATING STAFF IN RESTAURANT BUSINESS ESTABLISHMENTS: MATERIAL AND NON-MATTERIOR FACTORS OF EFFICIENCY - Гузар, Уляна; Тихоновський, Максим; Клос, Роман (SWorldJournal, 2025)
The article explores modern approaches to the formation of an effective system of staff motivation in restaurant establishments, taking into account a combination of material and intangible factors. The object of the study is the processes of motivating e